Conflitos e impactos socioambientais do turismo de segunda residência na vila de Barra Grande, no município de Vera Cruz - Bahia - Araújo, Mirela Carine Santos (2015)
Tourism is a multi-dimensional activity that contributes to the transformation of many communities. In Bahia, this activity on Itaparica island is characterized by a significant portion facing the second home tourism, since 1970, by to its proximity to Salvador. However, it is possible to see some social and environmental problems on the island. One of these problems motivated the research, that is, the identification of environmental degradation, explicit in the inadequate disposal of solid waste on the margins of, on the streets of villages and sandy beaches of Vera Cruz, one of two towns in Itaparica island. The area of this research is the village of Barra Grande, in Vera Cruz, as it is located near the largest hotel in the island, Club Med Itaparica; and also for expression in this village of second residence tourism. Thus, the general objective of the research is to understand the social-environmental conflicts caused by second-home tourism in Barra Grande. To achieve this goal, we opted for the literature search, exploratory and descriptive, with an interdisciplinary approach qualitative and quantitative. The research instruments used were book report, photographic records, semi-structured interviews and questionnaires applied to the main social actors (public managers, traders, residents and second home tourists). Finally, confirmed the hypothesis that there is a disarticulate between these social actors, generated by the absence of collective organization and integrated actions for tourism and the environment in Barra Grande, that impossibility the realization of a tourism with sustainability.